Prostitution: Allowed and stigmatized. Discursive perspectives from the life stories of six women who prostitute in El Trocadero - Gorenstein, Sharon (2013)
The social phenomenon of prostitution is immersed in a lot of situations, unfortunately most of them are invisible and obscured from the stigmas generated from the prevailing social and moral order. It is possible, however, within this range of situations, to interpret prostitution from the context of a former licensed brothel that, since the seventies, has given refuge to a large number of women who chose to work in prostitution. It is from this context that the investigation seeks to unravel a paradox situation from six depth interviews to women who prostitute in El Trocadero: women that even working in a legal brothel are socially stigmatized.